PENGETAHUAN IBU HAMIL TENTANG KELAS IBU HAMIL DI PUSKESMAS I DENPASAR TIMUR TAHUN 2018 - Sidiqkah, Amalia Iin (Jurnal Genta Kebidanan, 2019)
Abstract: Knowledge of Pregnant Women About Class of Pregnant Women. Class of pregnant women is a study group of pregnant women with activities in the form of joint learning, discussion and exchange of experiences on Maternal and Child Health (MCH), with a maximum participants of 10 people. From the ANC visit data in Puskesmas I Denpasar Timur in August 2018 there were 213 people who conducted ANC and only six people attended class for pregnant women. The purpose of this study was to determine the knowledge of pregnant women about the class of pregnant women based on age, education, employment, and parity. This type of research is descriptive, with a cross sectional approach, the study was conducted in Puskesmas I Denpasar Timur in January 2019, the study population was pregnant women who performed ANC with a sample of 32 people, this study used accidental sampling techniques, instruments used in collecting Research data are questionnaires, and univariate data analysis techniques. The results of research on knowledge of pregnant women about the class of pregnant women were obtained from 32 respondents, half (50%) had sufficient knowledge. Based on the age characteristics that have good knowledge, all (100%) are 20-35 years old. Based on the characteristics of education that has good knowledge, most (53.85%) of secondary education. Based on the characteristics of jobs that have good knowledge, most (53.85%) work and of parity with good knowledge, most (53.85%) primipara. Keyword: Knowledge, Pregnant Women, Class of Pregnant Women Abstrak: Pengetahuan Ibu Hamil Tentang Kelas Ibu Hamil. Kelas ibu hamil adalah kelompok belajar ibu hamil dengan kegiatan berupa belajar bersama, diskusi dan tukar pengalaman tentang kesehatan ibu dan anak (KIA), dengan jumlah peserta maksimal 10 orang. Dari data kunjungan ANC di Puskesmas I Denpasar Timur bulan Agustus 2018 terdapat 213 orang yang melakukan ANC dan hanya enam orang yang mengikuti kelas ibu hamil. Tujuan dari penelitian ini adalah untuk mengetahui pengetahuan ibu hamil tentang kelas ibu hamil berdasarkan umur, pendidikan, pekerjaan, dan paritas. Jenis penelitian ini adalah deskriptif, dengan pendekatan cross sectional, penelitian dilaksanakan di Puskesmas I Denpasar Timur pada bulan Januari 2019, populasi penelitian ini adalah ibu hamil yang melakukan ANC dengan jumlah sampel 32 orang, penelitian ini menggunakan teknik accidental sampling, instrumen yang digunakan dalam pengumpulan data penelitian adalah kuesioner, dan teknik analisa data univariat.Hasil penelitian pengetahuan ibu hamil tentang kelas ibu hamil didapatkan dari 32 responden, setengahnya (50%) memiliki pengetahuan cukup. Berdasarkan karakteristik umur yang memiliki pengetahuan baik, seluruhnya (100%) berumur 20-35 tahun. Berdasarkan karakteristik pendidikan yang memiliki pengetahuan baik, sebagian besar (53,85%) pendidikan menengah. Berdasarkan karakteristik pekerjaan yang memiliki pengetahuan baik, sebagian besar (53,85%) bekerja dan paritas yang memiliki pengetahuan baik, sebagian besar (53,85%) primipara. Kata Kunci: Pengetahuan,IbuHamil,KelasIbuHamil